Impact of Gender on Foreign Language Teaching Anxiety in the Republic of Serbia - Marinković, Ivana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The inconsistent and even contradictory results of the research on the impact of gender on foreign language teaching anxiety carried out so far worldwide, together with the lack of the research on this topic in the Republic of Serbia, formed the basis for this paper, aimed at exploring the influence in the context of Serbian foreign language teaching. There are no standardised instruments to measure this phenomenon, whereas the available ones mostly relate to students and pre-service foreign language teachers. Therefore, the instrument used comprised the scale designed by combining the items used in the accessible scales and by modifying them to meet the requests of this specific research. It also includes questions aimed at eliciting some demographic information on the respondents and open-ended questions aimed at eliciting the respondents’ opinion on the sources of foreign language teaching anxiety and potential ways of overcoming it. It was distributed via social networks of foreign language teachers in the Republic of Serbia; A total of 331 in-service teachers took part in the research. The quantitative data was analysed using the SPSS software package, whereas the content analysis technique was applied to the qualitative data. According to the results obtained, although a majority of foreign language teachers in Serbia are not familiar with the phenomenon of foreign language teaching anxiety, they do experience it to a moderate degree, whereas the foreign language teaching anxiety experienced by female teachers is significantly higher than that of their male counterparts. The difference is statistically significant in several situations covered by the research, all of which stem from foreign language teachers themselves, i.e., from their lack of self-confidence and unrealistic expectations with regard to achieving native-like fluency. These situations have the fear of public speaking and fear of making mistakes and being considered incompetent in common, and the fears can hardly be explained if viewed only from the perspective of applied linguistics, while neglecting sociolinguistics and gender studies. The interdisciplinary approach to this issue reveals that socio-cultural characteristics of the Serbian society, in which the foreign language teaching profession is still considered more convenient for women, thus boosting their instrumental motivation to learn foreign languages and achieve native-like fluency, might be one of the reasons. Moreover, foreign language teaching requires a great amount of public speaking on the part of teachers, and public conversations, even in the speaker’s native language, have proven to be more anxiety-provoking for women, who resort to private talks in order to find comfort in matching experiences (Tannen, 1990, p. 36). Finally, while women tend to talk about the problem of foreign language teaching anxiety, men tend to solve it by directly exposing themselves to anxiety-provoking situations at the expense of even quitting their job if they fail to overcome the anxiety. The fact that female teachers by far outnumber the male ones, and the fact that foreign language teaching anxiety increases foreign language learning anxiety, which is considered as the most detrimental affective factor in foreign language learning (Na, 2007), underline the importance of the phenomenon dealt with in this paper, which is completely neglected in our country, and highlight the necessity of raising foreign language teachers’ awareness of the issue.